2017
DOI: 10.1186/s12891-017-1712-0
|View full text |Cite
|
Sign up to set email alerts
|

Second opinion for degenerative spinal conditions: an option or a necessity? A prospective observational study

Abstract: BackgroundSecond opinions may improve quality of patient care. The primary objective of this study was to determine the concordance between first and second diagnoses and opinions regarding need for spinal surgery among patients with back or neck pain that have been recommended spinal surgery.MethodsWe performed a prospective observational study of patients who had been recommended for spinal surgery and received a second opinion between May 2011 and May 2012 at the Hospital Israelita Albert Einstein on the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 36 publications
1
54
0
3
Order By: Relevance
“…These changes in diagnosis or therapy and therefore agreement varied noticeably per independent specialist. Two-thirds non confirmed initial therapy recommendations and above 50% non confirmed initial diagnoses were also found by Lenza et al in their recent study from 2017 including patients referred for spinal surgery [18]. Another study showed that the second opinion can be influenced if the specialist has knowledge of the initial therapy recommendation [19].…”
Section: Discussionmentioning
confidence: 54%
“…These changes in diagnosis or therapy and therefore agreement varied noticeably per independent specialist. Two-thirds non confirmed initial therapy recommendations and above 50% non confirmed initial diagnoses were also found by Lenza et al in their recent study from 2017 including patients referred for spinal surgery [18]. Another study showed that the second opinion can be influenced if the specialist has knowledge of the initial therapy recommendation [19].…”
Section: Discussionmentioning
confidence: 54%
“…When compared to second opinions in other medical specialties, diagnostic value of second opinions in internal medicine is low. Studies in other medical specialties have shown that a new diagnosis is established in approximately 30-60% of patients, ranging from 30% in surgical oncology to 60% in orthopedic surgery [10,12,13,18,20,23,24]. This difference might be explained by the fact that, in this study and in previous studies [7,8], up to 85% of patients referred for a second opinion in internal medicine, had poorly defined conditions without a diagnosis at the time of referral.…”
Section: Plos Onementioning
confidence: 99%
“…Over the years, many studies in various medical specialties and multiple countries have shown that second opinions lead to the establishment of a new diagnosis in 2-60% [ 7 – 30 ] and a change in treatment in 20-60% of patients [ 8 19 , 21 , 22 , 24 27 , 31 ]. In addition, studies have shown that patients are generally satisfied with the process, even if it has not led to a new diagnosis or treatment [ 7 , 9 , 12 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 33,6 % der Fälle wurde die Operationsindikation bestätigt, wobei jedoch nur in 15 % die gleiche OP-Technik empfohlen wurde. 55 % wurde eine konservative Behandlung nahegelegt und in 11 % der Patienten konnte das Board keine spinale Pathologie feststellen [26]. Diese dramatischen Differenzen mögen nicht auf alle Regionen übertragbar sein, dennoch zeigen sie die Notwendigkeit für eine evidenzbasierte Überprüfung der Operationsindikationen.…”
Section: Zweitmeinungunclassified